LEGAL CONSTRUCTION OF NAMING AND CHARACTERISTICS OF SIMBEK AND TAMBAN SALAI FISH AS INTANGIBLE CULTURAL HERITAGE IN THE RIAU ISLANDS FROM A SOCIAL, ECONOMIC, AND CULTURAL PERSPECTIVE - Eva Amalia; Siti Arieta (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2026)
ABSTRACT This study analyzes the juridical construction of naming and characteristics of Salai Simbek and Tamban Salai as Intangible Cultural Heritage in the Kepulauan Riau Province, particularly in Natuna and Lingga Regencies. These traditional smoked fish products embody not only culinary heritage but also the collective identity of maritime communities. The research aims to examine the legal framework governing their protection and to formulate an appropriate legal protection model integrating cultural and economic dimensions. This research employs a normative juridical method with descriptive-analytical specifications and a qualitative approach. The study is based on statutory analysis, literature review, and secondary legal materials related to cultural advancement and intellectual property law. The findings reveal that registration under the Intangible Cultural Heritage (WBTb) regime provides cultural legitimacy; however, it does not fully ensure economic protection against unauthorized commercialization. The study concludes that a multi-layered protection model is necessary, combining WBTb recognition with geographical indications and/or collective trademarks. Comprehensive legal protection is essential to ensure legal certainty, communal justice, and sustainable economic development while preserving socio-cultural values within local communities. Keywords: Salai Simbek, Tamban Salai, Intangible Cultural Heritage, Normative Juridical ,Social Cultural and Economic Abstrak Penelitian ini menganalisis konstruksi yuridis penamaan dan karakteristik Salai Simbek dan Tamban Salai sebagai Warisan Budaya Takbenda (WBTb) di Provinsi Kepulauan Riau, khususnya di Kabupaten Natuna dan Kabupaten Lingga. Kedua produk ikan asap tradisional tersebut tidak hanya merepresentasikan kekayaan kuliner daerah, tetapi juga identitas kolektif masyarakat pesisir berbasis maritim. Penelitian ini bertujuan mengkaji kerangka hukum perlindungan terhadap penamaan dan karakteristiknya serta merumuskan model perlindungan hukum yang tepat secara kultural dan ekonomi. Metode penelitian yang digunakan adalah yuridis normatif dengan spesifikasi deskriptif analitis dan pendekatan kualitatif. Penelitian dilakukan melalui analisis peraturan perundang-undangan, kajian literatur, serta bahan hukum sekunder yang berkaitan dengan pemajuan kebudayaan dan hukum kekayaan intelektual. Hasil penelitian menunjukkan bahwa penetapan sebagai WBTb memberikan legitimasi kultural, namun belum sepenuhnya menjamin perlindungan ekonomi terhadap potensi komersialisasi oleh pihak luar. Kesimpulannya, diperlukan model perlindungan berlapis yang mengintegrasikan pengakuan WBTb dengan instrumen indikasi geografis dan/atau merek kolektif guna menjamin kepastian hukum, keadilan komunal, serta keberlanjutan ekonomi tanpa menghilangkan nilai sosial dan budaya masyarakat setempat. Kata Kunci: Salai Simbek, Tamban Salai, Warisan Budaya Takbenda, Yuridis Normatif, Sosial Budaya